The Application of Christian Religious Education Through Dinner Table Culture: An Analysis of Internalization and Spiritual Dialectics in Sentani Family - Labobar, Yohanes Kristian; Kopeuw, Philipus M. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze the application of Christian Religious Education (CRE) through the culture of "dining table" in Christian families in Ifar Besar, Sentani, Papua, and identify the spiritual dialectics that occur in the context of that culture. The background of this research is the shift of traditional values in society due to modernization, which has an impact on the decline in the quality of value and moral education in the family. The research method used is qualitative with an analytical description approach, involving the direct participation of family members involved in the practice of dining table culture. Data were collected through interviews, observations, and document analysis, which were then analyzed inductively and descriptively. The results of the study show that the integration of PAK with the local culture of the dining table contributes to the internalization of family, spiritual, and social values in Christian families in Ifar Besar. This process strengthens family relationships, fosters spiritual life, and helps families overcome the challenges of modernization. In addition, the culture of the dining table also creates a spiritual dialectic in the form of value reflection, spiritual transformation, and resolution of value conflicts and roles in the family. This research emphasizes the importance of local culture-based education in shaping children's character and moral values, as well as offering a relevant and effective educational model in the context of modernization.